Perbedaan Metode Ijtihad Nahdlatul Ulama dan Muhammadiyah dalam Corak Fikih di Indonesia - Isa Ansori (Nizham Jurnal Studi Keislaman, 2014)
There were different orientation in the background and methods of ijthad between Bahtsul Masail Nahdlatul Ulama (NU) and Majelis Tarjih Muhammadiyah (The Muhammadiyah Legal Affairs Committee). The ijtihad orientation of Bahtsul Masail emphasizes on cultural approach to maintain the previous values that have been good, and take the new values better. This approach accepts local culture and wisdom as part of the past products that has no conflict with al-Qur’an and al-Hadith, or by changing the content of culture and local wisdom with Quranic and Sunnah content. This approach is different from the ijtihad orientation model developed by Majelis Tarjih Muhammadiyah called "tajdid". With this approach, Majelis Tarjih Muhammadiyah attempts to recover and purify Islam according to its original teachings. With its popular jargon "Back to the Qur'an and al-Sunnah" seeks to purify Islam from contamination of Takhayyul, Bid’ad (Heresy) and Churafat (TBC). The differences on ijtihad orientation between Bahtsul Masail NU and Majelis Tarjih Muhammadiyah had an impact on the difference of ijtihad methods used. The ijtihad method of Bahtsul Masail more conservative and walk to the progressive-moderate atmosphere by trying to adjust the changing of socio-cultural of community, through the use of ijtihad method Qouly, Ilhaqy, Taqriry, and Manhajy. While the ijtihad method used by Majelis Tarjih Muhammadiyah moves towards Progressive-Dynamic atmosphere by using contemporary ijtihad method like Bayani, ta'lili, and istishlahi with an interpretation approach At-tafsir al-ijtima'i al-mu'asir (hermeneutic), at-Tarikhiyah (historical), as-Susiulujiyyah (sociological) and; al-antrubulujiyyah (anthropological) and using ijtihad techniques Ijma', Qiyas, Masalih mursalah, and Urf.